POST HARVEST PHYSICAL QUALITIES OF POTATO CULTIVARS AS INFLUENCED BY STORAGE CONDITIONS - Salil, B.; Naik, K. R.; Basavaraj, N. (Potato Journal, 2013)
The studies were conducted at Dharwad during 1999-2000 to assess the influence of different storage condition on post harvest physical qualities of potatoes. The study indicated that the tubers stored under zero energy cool chamber (ZECC) maintained significantly lower physiological loss in weight (PLW 8.54%) and percent tuber rotting after four months of ZECC storage compared 14.00 percent PLW under ambient condition. Among the varieties PLW% after four months was lower (7.75%) in cv. Kufri Chandramukhi and higher (14.46%) in cv. Kufri Sutlej. The storage condition, variety and period interaction was significant for PLW(%). Lower cumulative PLW (%) after four months under ZECC and ambient condition were recorded in cv. Kufri Chandramukhi, (6.83 and 8.67% respectively) where as cv. Kufri Sutlej recorded higher values (11.25 and 11.67% respectively). The lower PLW (%) in ZECC stored tubers was due to low transpiration and respiration rate because of low temperature and with humidity inside ZECC It is known that PLW more than 10 per cent makes potato unmarketable due to unattractive and shriveled appearance. PLW of tubers under ZECC in present study was well below this limit.